Implementation status of morbidity and mortality conferences in Swiss hospitals: a national cross-sectional survey study. (16th January 2018) - Praplan-Rudaz, Isabelle; Pfeiffer, Yvonne; Schwappach, David L B
Abstract: Objective: To determine the implementation status and current practice of morbidity and mortality conferences (M&MCs) in Switzerland. Design: A national cross-sectional online survey was conducted in spring 2017. The questionnaire focused on overall goals, structure and procedures of hospital M&MCs. Further topics included satisfaction, perceived effectiveness and support requirements. Setting: A total of 913 chief physicians of surgery and internal medicine, and specialist fields of obstetrics and gynaecology, anaesthesiology and intensive care from Swiss acute care hospitals were invited to the survey. 321 completed the questionnaire, resulting in a 35.2% response rate. Participants: Chief or senior physicians in charge of the M&MCs in their department. Intervention: No intervention Main Outcome Measures: Numbers and percentages of M&MCs within the surveyed disciplines fulfilling certain characteristics and procedural features. Results: Among 321 respondents, the majority are conducting M&MCs in their departments. Within and between the medical disciplines considerable heterogeneity was found in structural and procedural features of M&MCs. Only a small part of the reported M&MCs is following a systematic approach and meeting recommended procedural features. Although the respondents are satisfied and perceive the M&MCs as an efficient tool, they agree that there is a need for professionalization and standardization. Conclusion: M&MCs are widely used to promote medical education, patient safety and quality improvements. However, the term M&MC seems to cover different types of meetings. Although the overall goals are similar, various types of M&MCs are used in practice and different objectives are pursued. Tools such as checklists, guidelines and templates are considered helpful.